1982
DOI: 10.1590/s0074-02761982000400010
|View full text |Cite
|
Sign up to set email alerts
|

Incapacidade de evolução do Trypanosoma cruzi na hemocele de triatomíneos

Abstract: O exame da hemolinfa de triatomíneos (Triatoma infestans e Dipetalogastermaxima) infectados pelo Trypanosoma cruzi há 10, 15, 20 e 30 dias não revelaram a presença do flagelado. Material colhido e lavado da hemocele de D. maxima infectados, também foi negativo. A inoculação de formas sanguíneas do parasita e daquelas obtidas do conteúdo intestinal de triatomíneos na hemocele revelou que os parasitas não foram capazes de manter na hemolinfa uma infecção por mais de 40 dias e que não puderam penetrar no intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The first report about anti-trypanosome factors in triatomid hemolymph was published by Alvarenga and Bronfen (1982) who observed T. cruzi's inability biological activity of GF-1, GF-2, GF-3 and GF-4 fractions on Trypanosoma rangeli KP1(-). 100 µl of each fraction were incubated with an equal volume of parasites containing 1x10 7 flagellates/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The first report about anti-trypanosome factors in triatomid hemolymph was published by Alvarenga and Bronfen (1982) who observed T. cruzi's inability biological activity of GF-1, GF-2, GF-3 and GF-4 fractions on Trypanosoma rangeli KP1(-). 100 µl of each fraction were incubated with an equal volume of parasites containing 1x10 7 flagellates/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Alvarenga & Bronfen [ 18 ] made the first observation of lytic activity against T . cruzi in the hemolymph in two triatomine species: Dipetalogaster maxima and Triatoma infestans .…”
Section: Discussionmentioning
confidence: 99%
“…Alvarenga & Bronfen [18] made the first observation of lytic activity against T. cruzi in the hemolymph in two triatomine species: Dipetalogaster maxima and Triatoma infestans. These researchers revealed that the parasites inoculated into the hemocoel of the insects did not survive after a few days, evidencing the inability of T. cruzi to establish itself in hemolymph.…”
Section: Lytic Activity and Proteomic Analysis Of Hemolymphmentioning
confidence: 99%